2022
DOI: 10.1021/acs.jafc.1c07241
|View full text |Cite
|
Sign up to set email alerts
|

Tangeretin Inhibits BACE1 Activity and Attenuates Cognitive Impairments in AD Model Mice

Abstract: Tangeretin (TAN) exhibits many bioactivities, including neuroprotective effects. However, the efficacy of TAN in Alzheimer’s disease (AD) has not been sufficiently investigated. In the present study, we integrated behavioral tests, pathology assessment, and biochemical analyses to elucidate the antidementia activity of TAN in APPswe/PSEN1dE9 transgenic (Tg) mice. At supplementation levels of 100 mg/kg body weight per day, TAN significantly attenuated the cognitive impairment of Tg mice in behavioral tests. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…[ 42 ] Thus, once the loaded nanoparticle is internalized, IRW could prevent NFκB translocation into the nuclei, both in cancer and endothelial cells. [ 17,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 ] Thus, once the loaded nanoparticle is internalized, IRW could prevent NFκB translocation into the nuclei, both in cancer and endothelial cells. [ 17,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that TAN treatment (100 mg/kg body weight/day) significantly ameliorated the cognitive dysfunction and reduced amyloid beta (Aβ) aggregation and synaptic loss in an APPswe/PSEN1dE9 transgenic (Tg) mice AD model. A mechanistic study revealed that TAN could inhibit β-secretase in both in vitro and in vivo studies, proving TAN's potential role in the management of AD pathogenesis [22].…”
Section: Effect Of Tan In Ad Modelsmentioning
confidence: 99%
“…Although research on the beneficial effects of TAN in relation to AD and AD pathology are limited, some of the published data indicate that it can play a positive role in the management of AD pathology. In recent study by Shu et al at the Institutes of Biomedical Sciences, School of Medicine, Jianghan University, China, the effects of TAN in an AD model of mice were evaluated [22]. The authors found that TAN treatment (100 mg/kg body weight/day) significantly ameliorated the cognitive dysfunction and reduced amyloid beta (Aβ) aggregation and synaptic loss in an APPswe/PSEN1dE9 transgenic (Tg) mice AD model.…”
Section: Effect Of Tan In Ad Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, dozens of PMFs have been isolated and identified from citrus plants, and their types and contents are different with the type of citrus species [ 1 ]. Tangeretin (5,6,7,8,4′-pentamethoxyflavone, TAN), one of the most abundant PMFs in citrus peel, has been reported to possess several biological activities, including anti-oxidative, anti-inflammatory, hepatoprotective, neuroprotective, anti-obesity, and anticancer effects [ 2 , 3 , 4 , 5 , 6 , 7 ]. Certain studies in previous years have shown that 5-hydroxylated PMFs formed during storage by the autohydrolysis of PMFs in citrus fruits exhibited more potent bioactivities than their PMF counterparts [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%